2021
DOI: 10.1109/jeds.2021.3117794
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Horizontally Aligned Perovskite Nanowire LED With Improved Light Extraction

Abstract: Within a short span of a few years, metal halide perovskite light-emitting diodes have shot past the 20 percent external quantum efficiency mark. As the material quality and photoluminescent quantum yield of perovskite are already at par with the state-of-the-art, light extraction for further quantum efficiency enhancement has taken the center stage of scientific interest. Herein, we demonstrate horizontally aligned perovskite nanowire-based light-emitting diodes with 50.9 percent of light extraction efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The enhanced resonance in perovskite NWs can be used not only in laser but also in LED, as reported by Fan and co‐workers previously ( Figure 9 a). [ 161 ] It was demonstrated that horizontally aligned MHP NWs had 50.9% light extraction efficiency, with a 2.9‐fold increase over the planar counterpart. It was induced by NWs antenna effect, resulting in a resonance peak of 530 nm, for NWs with diameters of 300, 500, and 550 nm, respectively.…”
Section: Investigation On Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhanced resonance in perovskite NWs can be used not only in laser but also in LED, as reported by Fan and co‐workers previously ( Figure 9 a). [ 161 ] It was demonstrated that horizontally aligned MHP NWs had 50.9% light extraction efficiency, with a 2.9‐fold increase over the planar counterpart. It was induced by NWs antenna effect, resulting in a resonance peak of 530 nm, for NWs with diameters of 300, 500, and 550 nm, respectively.…”
Section: Investigation On Materials Propertiesmentioning
confidence: 99%
“…Reproduced with permission. [ 161 ] Copyright 2021, IEEE. b) Polarized emission preference: Fourier images showing the angular emission from a nanowire bundle in the printed horizontal (left) and a vertical (middle) filament on a glass slide, and the polarized emission of printed nanowire composites (right).…”
Section: Investigation On Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation